2012
DOI: 10.1002/humu.22106
|View full text |Cite
|
Sign up to set email alerts
|

A novel classification system to predict the pathogenic effects of CHD7 missense variants in CHARGE syndrome

Abstract: CHARGE syndrome is characterized by the variable occurrence of multisensory impairment, congenital anomalies, and developmental delay, and is caused by heterozygous mutations in the CHD7 gene. Correct interpretation of CHD7 variants is essential for genetic counseling. This is particularly difficult for missense variants because most variants in the CHD7 gene are private and a functional assay is not yet available. We have therefore developed a novel classification system to predict the pathogenic effects of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 69 publications
3
46
1
Order By: Relevance
“…Although we only have detailed information on the variant in CHD7 for 23 patients, the fact that all reported variants lead to a premature stop in CHD7 is interesting, because truncating CHD7 variants are in general associated with a more severe phenotype. 12 Are certain phenotypic features more common in our collected cohort?…”
Section: Immunological Abnormalities Reported In Charge Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Although we only have detailed information on the variant in CHD7 for 23 patients, the fact that all reported variants lead to a premature stop in CHD7 is interesting, because truncating CHD7 variants are in general associated with a more severe phenotype. 12 Are certain phenotypic features more common in our collected cohort?…”
Section: Immunological Abnormalities Reported In Charge Syndromementioning
confidence: 99%
“…There is no clear genotype-phenotype correlation, but variants leading to a premature stop codon are, in general, associated with a more severe phenotype than variants with a non-truncating effect, that is, missense variants. 12 Since the genetic cause of CHARGE syndrome was identified, its phenotype has been further explored. In addition to the above symptoms, other common clinical features of CHARGE syndrome are: absent or hypoplastic semicircular canals, cranial nerve dysfunction (including facial nerve palsy), cleft lip and/or palate, anosmia, feeding difficulties and skeletal abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Some variants may be erroneously interpreted as disease-causing. An interpretation algorithm for missense variants has been published by Bergman et al 6 2.3 Clinical sensitivity (proportion of positive tests if the disease is present)…”
Section: Analytical Specificity (Proportion Of Negative Tests If the mentioning
confidence: 99%
“…The clinical specificity of these criteria is~85%, as 14-17% of the patients with a CHD7 disease-causing variant do not completely fulfill these criteria. 4 Bergman et al 6 defined criteria for CHD7 testing and showed that if these criteria were used the risk of not offering the test to a patient with a CHD7 disease-causing variant was extremely low. 4 But, it should be taken into account that the mild end of the phenotypic spectrum is still expanding.…”
Section: Analytical Specificity (Proportion Of Negative Tests If the mentioning
confidence: 99%
“…On the basis of the prediction programs (score +2) and de novo occurrence (score +3), this missense variant probably affects function according to the scoring classification published by Bergman. 15 In Patient 3, CHD7 sequencing revealed an intronic variant predicted to disrupt the exon 6 donor splice site (c.2442+5G4C; NM_017780.3; g.127819G4C; NG_007009.1). The same variant was present in his affected older brother 9 and their mildly affected father.…”
Section: Methodsmentioning
confidence: 98%